FRI0352 Damage accrual in a large monocentric cohort of primary sjÖgren's syndrome patients: determinants and impact on patient reported outcomes. (12th June 2018) - Baldini, C.; Ferro, F.; Luciano, N.; Calabresi, E.; Elefante, E.; Mosca, M.; Bombardieri, S.
Abstract : Background: Primary Sjögren's Syndrome (pSS) is a chronic progressive disease potentially leading to irreversible organ damage. To date only a limited number of studies have analysed prevalence and factors associated with damage accrual in pSS. Objectives: a) to characterise cumulative damage in pSS patients, b) to identify determinants associated with its presence and c) to evaluate the impact of damage on patient reported outcomes (PROs). Methods: Data from a monocentric cohort of 466 pSS patients were analysed. Glandular and extra-glandular damage manifestations were assessed by the Sjögren's Syndrome Disease Damage Index (SSDDI). Additional items of damage defined 'a priori' as being potentially related to treatment (i.e osteoporosis, diabetes, infections) were analysed separately. The EULAR Sjögren's Syndrome Disease Activity Index (ESSDAI) was used to measure disease activity at baseline and prospectively during the follow-up. The EULAR Sjogren's Syndrome Patient Reported Index (ESSPRI), Oral Health Impact Profile (OHIP) and Ocular Surface Disease Index (OSDI) were utilised to record PROs. Patients' comorbidities were assessed by the Charlson Comorbidity Index (CCI). Results: A total of 466 pSS patients (446 F:20 M, median age (IQR): 59 years (48–69) were included in the study. The frequency of anti-Ro-SSA in the cohort was 69.5% (324/466). The median ESSDAI was 4 (IQR 1–8) at baseline and 2 (IQR 0–5) at the last evaluation, respectively. In addition to symptomatic agents, patients had been treated during the disease course with low-medium doses of glucocorticoids (GCs) (56%), hydroxychloroquine (HCQ) (62%) and DMARDs (16.6%). After a median follow-up of 5 years (IQR, 2–10), 208 patients (44.6%) had accrued some damage in either the oral damage items (33%), ocular damage items (20%) and/or systemic damage items (12%). In addition, 24/466 patients had developed a non-Hodgkin lymphoma and 2 patients a multiple myeloma. The SSDDI score ranged from 0 to 14. In the regression analysis: patients more likely to develop damage were those that were older, with a longer disease duration, higher baseline ESSDAI and who had been treated with DMARDs, whereas patients who had been ever treated with HCQ were less likely to develop disease-related damage. Similarly, treatment-related damage was independently associated with: disease duration, age of the patients, baseline ESSDAI, anti-Ro/SSA positivity and use of GCs. Oral and ocular damage items significantly correlated with ESSPRI, OHIP and OSDI, whereas systemic damage items positively correlated with patients CCI. Conclusions: This large pSS cohort confirmed that demographic and clinical characteristics as well as medication are independently associated with disease-related and treatment-related damage. In particular, this study shows a highly significant impact of baseline disease activity on the development of future damage and poor PROs in pSS patients. Disclosure of Interest: None declared